Ninguém tira o trono do estudar: uma avaliação das ações desenvolvidas no IFCE Campus Itapipoca para a promoção da permanência e do êxito acadêmicos - Souza, Miliany Michelly Barreto de (2020)
This research addresses the evaluation of actions carried out by the Federal Institute of Education, Science and Technology of Ceará (IFCE), Itapipoca campus, to promote student permanence and success. The actions are guided by IFCE’s 2017-2024 Strategic Plan for Student Permanence and Success (PPE). As a participatory evaluative research, according to the model proposed by Silva (2012), we seek to include the participation of students in the production of knowledge about public policy that they enjoy, so that they indicate the effectiveness of the actions developed. Student participation in policy assessment makes it possible to design defense strategies for the campus, in order to resist the context of political and economic hardships faced since 2016. To perform the proposed assessment, we sought to investigate the historical, economic and political context of the implementation of IFCE’s Itapipoca campus; to know how the campus works and how the Plan for Student Permanence and Success has been worked on; and to identify the profile of students benefiting from the actions for student permanence and success. The course of this research was based on authors critical to the capitalist hegemonic model. Their theories were used to build analyses about the outlines of public policies in Brazil, the unfolding of inequalities in Professional and Higher Education, influenced by the dominance of slavocracy, and the role of education as a potential tool for social transformation from the current inequality state to a state with social rights guaranteed, as long as it is aimed towards the interests of the people. The methodological course of this participatory evaluative research used the Case Study method and holds a qualitative character with quantitative contributions. Data was collected from documents and interviews with managers and representatives of the Local Commission on Student Permanence and Success, as well as from questionnaires and focus groups carried out with students. This study allowed us to identify the factors that assert students' permanence and the factors that demand more attention in the strategy to attend the public. Results point to the need to encourage dialogue between the academic community and the students' organized participation in the daily decisions of the institution, so that they familiarize themselves with the challenges faced and so that joint actions conducive to the material and symbolic permanence of students are designed.